Hubungan Resiliensi dengan Kualitas Hidup pada Pasien Kanker Payudara yang Menjalani Kemoterapi di Rumah Sakit Islam Sultan Agung Semarang - Maitsa Novia Ramandhani; Retno Setyawati; Erna Melastuti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the relationship from resilience also qualities of life among breast cancer clients undergoing chemotherapy at Sultan Agung Islamic Hospital, Semarang. A quantitative cross-sectional design was included to 67 patients selected from accidental sample. Resilience was measured by Connor–Davidson Resilience Scale, while qualities of life was assessed using by EORTC QLQ-C30 instrument. Univariate analysis demonstrated that most patients exhibited moderate levels of resilience and quality of life. Bivariate analysis using Somers’ d revealed a strong and statistically significant also positive association from resilience then qualities of life (r = 0.629; p = 0.001). These shows indicate the higher resilience is consistently associated with better multidimensional quality of life during chemotherapy. The answers supporting the theoretical proposition that resilience functions as a central adaptive resource that modulates psychological distress, social functioning, and perceived health status. This study highlights the importance of integrating resilience-oriented psychosocial interventions into routine oncology care. Strengthening resilience is therefore essential not only for improving subjective well-being but also for optimizing comprehensive treatment outcomes in breast cancer clients undergoing long-term chemotherapy.